DATACRACY IN BUILDING MELIKAN VILLAGE, EFFORTS OUT OF EXTREME POVERTY - Adji Suradji Muhammad; B. Hari Saptaning Tyas; Condrodewi Puspitasari; Juang Gagah Mardhika; Maulana Chandra Atmajha (International Journal of Social Science, 2022)
As one of the villages that fall into the category of extreme poor, Melikan Village in Klaten Regency must start using data in planning development. This study aims to explore how the Melikan Village Government utilizes the SDG's Village data in preparing development plans. The method used in this research is qualitative with an interpretative approach. The informants selected were the Village Head, Village Secretary, Heads of Affairs and Section Heads, BPD Chairs and Members, youth leaders and community leaders. The results showed that the Melikan Village Government did not know from where the data sources used by the supra-village government in determining the village poverty level came from. Even the village head questioned the source of the data used to determine Melikan as a village with an extreme category. The real conditions in Melikan Village do not show any indicators of extreme poverty. In development planning, Melikan Village has not been based on data because it prioritizes the village deliberation process. Melikan Village conducts the SDG's Village data collection process which can be used as a basis for future development planning by prioritizing the first goal of SDG's Desa, namely a village without poverty.